Education for sustainable development and climate change education: the potential of social network analysis based on twitter data - Goritz, A.; Kolleck, N.; Jörgens, H. (Sustainability, 2019)
Education is considered as an essential tool for achieving sustainability-related goals. In this regard, Education for Sustainable Development (ESD) and Climate Change Education (CCE) have become prominent concepts. Central characteristics of both concepts influence the non-hierarchical network governance structure that has formed around them: (1) their international origin, (2) the conceptual ambiguity that surrounds them, and (3) the limited implementing power of international organizations, who developed these concepts. Hence, networks are essential to ESD and CCE, however, only few studies have used Social Network Analysis (SNA) techniques to analyze their governance structure. The aim of this article is to illustrate how to use SNA, based on Twitter data, as an approach to examine the governance structure that has developed around ESD and CCE. We conduct an illustrative SNA, using Twitter data during three global climate change summits (2015-2017) to examine CCE-specific debates and identify actors exerting the most influence. We find that international organizations and international treaty secretariats are most influential across all years of the analysis and moreover, are represented most often. These findings show that using SNA based on Twitter data offers promising possibilities to better understand the governance structure and processes around both concepts.